Maternal Passive Immunity and Dengue Hemorrhagic Fever in Infants - Adimy, Mostafa; Mancera, Paulo F. A. [UNESP]; Rodrigues, Diego S.; Santos, Fernando L. P. [UNESP]; Ferreira, Cláudia P. [UNESP] (Springer Nature, 2020)
Dengue hemorrhagic fever (DHF) can occur in primary dengue virus infection of infants < 1 year of age. To understand the presumed role of maternal dengue-specific antibodies received until birth in the development of this primary DHF in infants, we investigated a mathematical model based on a system of nonlinear ordinary differential equations that mimics cells, virus and antibodies interactions. The neutralization and enhancement activities of maternal antibodies against the virus are represented by a function derived from experimental data and knowledge from the medical literature. The analytic study of the model shows the existence of two equilibriums, a disease-free equilibrium and an endemic one. We performed the asymptotic stability analysis for these two equilibriums. The local asymptotic stability of the endemic equilibrium (DHF equilibrium) corresponds to the occurrence of DHF. Numerical results are also presented in order to illustrate the mathematical analysis performed, highlighting the most important parameters that drive model dynamics. We defined the age at which DHF occurs as the time when the infection takes off that means at the inflection point of the curve of infected cell population. We showed that this age corresponds to the one at which maximum enhancing activity for dengue infection appears. This critical time for the occurrence of DHF is calculated from the model to be approximately 2 months after the time for maternal dengue neutralizing antibodies to degrade below a protective level, which corresponds to what is observed in the experimental data from the literature.
Keywords: Antibody-dependent enhancement (ADE); DENV; Local and global stability analyses; Mathematical modeling